2016
DOI: 10.5812/ijp.6358
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Asthma and Allergic Rhinitis in Children with Celiac Disease

Abstract: Background: Celiac disease is an autoimmune disorder characterized by damage to the small intestinal mucosa following the intake of glutencontaining foods in genetically predisposed individuals. Studies suggest that celiac disease is associated with asthma and allergic rhinitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…It has been shown that atopy is found in coeliac patients, but it is still unclear whether this coexistence is to be considered coincidental or an expression of a real association. Several case-control studies (23,24) failed to demonstrate an increased prevalence of atopic conditions in children with CD when compared to controls. On the other hand, Kero et al (25) reported a cumulative incidence of asthma in children with CD (24.6%) significantly higher than in children without CD (3.4%; P<0.001) and Ress et al (26) showed that CD prevalence in children with active atopic dermatitis was more than four times as high as in randomly selected children.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that atopy is found in coeliac patients, but it is still unclear whether this coexistence is to be considered coincidental or an expression of a real association. Several case-control studies (23,24) failed to demonstrate an increased prevalence of atopic conditions in children with CD when compared to controls. On the other hand, Kero et al (25) reported a cumulative incidence of asthma in children with CD (24.6%) significantly higher than in children without CD (3.4%; P<0.001) and Ress et al (26) showed that CD prevalence in children with active atopic dermatitis was more than four times as high as in randomly selected children.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, no relationship was discovered between diet coherence and olfactory functions and nasal cells. 30…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact causes of concomitance are unknown but their common prevalence have surely been discussed in the recent years. [19][20][21][22] A study from Switzerland 21 having large number of cases with CD as well controls found an increased hazard ratio of asthma as 1.61 (95% CI: 1.50-1.72) for cases with CD. Incidence of hospitalization was significantly raised in cases having CD and asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Common genetic as well as environmental factors have been argued to be the causes of CD along with asthma. Kero and colleagues 22 showed that the risk of asthma was 7.26 times increased in cases who had been diagnosed with CD. Zauli and coworkers 24 found a positive association of CD with atopy and noted that an overall prevalence of 1% amongst atopic cases in Italy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation